Antimicrobial Activity of Fractions of Ethyl Acetate Extract of Cladosporium oxysporum, An Endophytic Fungus Derived from Alyxia reinwardtii - Hartanti, Dwi; Supriyanto, July; Sugijanto, Noor Erma N (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
The endophytic fungi Cladosporium oxysporum was isolated from medicinal plants Alyxia reinwardtii. The antimicrobial activity of fractions of ethyl acetate extract and also antioxidant and antimicrobial activities of fraction 7 of ethyl acetate extract of (AR-7) were determined in this study. Antimicrobial activity was determined by TLC bioautography and disc diffusion methods. Antioxidant activity was determined by TLC DPPH autography assay. The fractions of ethyl acetate extract of C. oxysporum at dose of 100 mg/ml were active as antimicrobial against S. aureus, E. coli and C. albicans in disc diffusion method test. Fraction AR-7 was active as antioxidant in TLC-DPPH autography assay. Fraction AR-7 was active as antimicrobial against S. aureus, but was not active against another tested microoorganisms in TLC-bioautography